ANALISIS PERTUMBUHAN ALLOMETRI DAN INDEKS KONDISI CAESIO CUNNING DIDAPATKAN DARI HASIL TANGKAPAN NELAYAN KOTA TARAKAN - Gazali Salim (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2015)
Caesio Cunning is one type of fish that has a lot of potential one of which is a protein, where in the protein content of Caesio Cunning in the test using the wet weight of 30.861% and 77.1151% of the dry weight. The aim of the study was to analyze biotehniques of the growth model allometry and the index conditions of Caesio Cunning. The research method uses descriptive method. The scope of this study is variable allometry growth and condition index of Caesio Cunning. Data collection techniques using survey research design. Caesio Cunning sampling technique using purposive sampling method. Making a total of 12 times sampling, each sampling expect a maximum of 15 birds in the sample can already be representative of the population Caesio cunning in the waters city of Tarakan.Results of studies using growth models allometri to Caesio cunning male sex in getting value b 2.9024 is allometri negative and for female sex obtained b value 1.9083 is allometri negative. Percentage value index model Caesio cunning condition of the male sex flattened body shape obtained by 61.73%, proportional body shape of 2.47%, the shape of the body is fat by 32.1% and the shape of the body is very fat by 3.7%; while the index of the condition of the female sex flattened body form obtained percentage of 56.57%, proportional body shape amounted to 5.05%, the body shape of 34.34% body fat and body shape very fat at 4.04%.Keywords : Caesio Cunning, Allometri growth and condition index, Tarakan